2013
DOI: 10.1159/000350836
|View full text |Cite
|
Sign up to set email alerts
|

In Patients with Colorectal Cancer, Preoperative Serum Interleukin-6 Level and Granulocyte/Lymphocyte Ratio Are Clinically Relevant Biomarkers of Long-Term Cancer Progression

Abstract: Objective: To investigate the clinical significance of the serum inflammatory cytokines and the blood granulocytes/lymphocytes (G/L) ratio in patients with colorectal cancer. Methods: Forty-six patients underwent surgery for colorectal cancer. The G/L ratio and serum inflammatory cytokines including interleukin (IL)-1β, IL-6, IL-8, tumour necrosis factor-α (TNF-α), granulocyte colony-stimulating factor and macrophage colony-stimulating factor (M-CSF) were measured before surgery and correlated with the Tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 61 publications
1
28
0
1
Order By: Relevance
“…Other studies have described similar results (Shimazaki et al, 2013;Stanilov et al, 2014). However, there was no association between TNF-α levels and -308G>A and -238G>A polymorphism haplotypes in Mexican CRC patients and controls.…”
Section: Discussionsupporting
confidence: 55%
“…Other studies have described similar results (Shimazaki et al, 2013;Stanilov et al, 2014). However, there was no association between TNF-α levels and -308G>A and -238G>A polymorphism haplotypes in Mexican CRC patients and controls.…”
Section: Discussionsupporting
confidence: 55%
“…Elevated levels of IL6 are associated with poor prognosis in cancers of the lung, colon, kidney, bladder, and others (28)(29)(30). Thus, therapeutics targeting IL6 and IL6 signaling components are also being tested in clinical trials for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have indicated that peripheral blood lymphocytes level has a close relationship with the malignancy. Now, it is clear that peripheral blood lymphocytes level or its ratios are not only correlate with survival of patients with cancers such as glioblastoma multiforme, renal cell carcinoma, colorectal, uterine cervix and breast cancers (Riesco et al, 1970;Bambury et al, 2013;Fox et al, 2013;Shimazaki et al, 2013), but also with tumor recurrence in bladder cancer, head and neck squamous cell carcinoma (O'Toole and Unsgaard, 1979;Kuss et al, 2004). Galon et al (2012) demonstrated that T-cell infiltrates could be considered as a stronger independent prognostic factor than the conventional clinicopathological factors such as tumor size, depth of infiltration, tumor differentiation, or the nodal status.…”
Section: Figure 1 Impact Of Pretherapeutic Lymphocyte Ratio On 5-yeamentioning
confidence: 99%